The Role of Information Technology in the Development of Education Management Systems in the Digital Age: A Literature Review - Suhardi, Muhamad; Fahmi, Agus (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Digital transformation has become a major driver in the development of education management systems in the modern era. This study aims to examine the role of information technology in improving the effectiveness, efficiency, and accountability of education management. The study was conducted using a qualitative descriptive approach through a review of literature from various relevant recent studies. The study results indicate that the digitization of education management information systems (EMIS) contributes significantly to accelerating data management, strengthening data-driven decision-making, and improving administrative transparency. Technology also plays an important role in strengthening teacher competencies through the use of digital platforms and online learning systems. However, challenges such as infrastructure limitations, the digital divide, and data security issues remain serious obstacles to its implementation. Looking ahead, the use of cutting-edge technologies such as big data, artificial intelligence (AI), and the Internet of Things (IoT) has great potential in shaping a more responsive and adaptive education management system. Therefore, a comprehensive and sustainable strategy is needed to support equitable and ethical digitalization of education management. Keywords: Information Technology, Education Management System, Education Digitalization